Penumbra Consumption Rates Based on Time-to-Maximum Delay and Reperfusion Status: A Post Hoc Analysis of the DEFUSE 3 Trial. Issue 8 (August 2021) - Yaghi, Shadi; Raz, Eytan; Dehkharghani, Seena; Riina, Howard; McTaggart, Ryan; Jayaraman, Mahesh; Prabhakaran, Shyam; Liebeskind, David S.; Khatri, Pooja; Mac Grory, Brian; Al-Mufti, Fawwaz; Lansberg, Maarten; et al.
Abstract : Background and Purpose: In patients with acute large vessel occlusion, the natural history of penumbral tissue based on perfusion time-to-maximum (Tmax ) delay is not well established in relation to late-window endovascular thrombectomy. In this study, we sought to evaluate penumbra consumption rates for Tmax delays in patients with large vessel occlusion evaluated between 6 and 16 hours from last known normal. Methods: This is a post hoc analysis of the DEFUSE 3 trial (The Endovascular Therapy Following Imaging Evaluation for Ischemic Stroke), which included patients with an acute ischemic stroke due to anterior circulation occlusion within 6 to 16 hours of last known normal. The primary outcome is percentage penumbra consumption, defined as (24-hour magnetic resonance imaging infarct volume–baseline core infarct volume)/(Tmax 6 or 10 s volume–baseline core volume). We stratified the cohort into 4 categories based on treatment modality and Thrombolysis in Cerebral Infarction (TICI score; untreated, TICI 0-2a, TICI 2b, and TICI3) and calculated penumbral consumption rates in each category. Results: We included 141 patients, among whom 68 were untreated. In the untreated versus TICI 3 patients, a median (interquartile range) of 53.7% (21.2%–87.7%) versus 5.3% (1.1%–14.6%) of penumbral tissue was consumed based on Tmax >6 s ( P <0.001). In the same comparison for Tmax >10 s, we saw a difference of 165.4% (interquartile range, 56.1%–479.8%) versus 25.7% (interquartile range, 3.2%–72.1%; P <0.001). Significant differences were not demonstrated between untreated and TICI 0-2a patients for penumbral consumption based on Tmax >6 s ( P =0.52) or Tmax >10 s ( P =0.92). Conclusions: Among extended window endovascular thrombectomy patients, Tmax >10-s mismatch volume may comprise large volumes of salvageable tissue, whereas nearly half the Tmax >6-s mismatch volume may remain viable in untreated patients at 24 hours. Abstract : Supplemental Digital Content is available in the text.